Generational Aspects of Medicare - Cutler, David M; Sheiner, Louise (American Economic Review, 2000)
This paper examines the generational aspect of the current Medicare system and some stylized reforms. We find that the rates of return on Medicare for today's workers are higher than those for Social Security and that the Medicare system is shifting a greater share of the burden on future workers than is Social Security. Nonetheless, the rates of return on Medicare, using the Medicare Trustees assumptions, are still not that high–roughly 2 percent for today's youngest workers. But forecasting future Medicare expenditures is quite difficult. Under an alternative higher-cost baseline, which we consider plausible, rates of return for today's youngest workers will exceed 3 percent. Putting Medicare on a sustainable basis by raising the payroll tax or reducing benefits would greatly reduce the rate of return for today's workers. Under the Trustees assumptions, for example, the payroll tax would have to be increased by 2.0 percent of payroll to put the Medicare system in balance in perpetuity. This policy would reduce the rate of return on today's youngest workers to about 1.3 percent.